When 9 is not on the right: implications from number-form synesthesia. - Gertner, L; Henik, A; Cohen Kadosh, R (2009)
Number-form synesthetes consciously experience numbers in spatially-defined locations. For non-synesthete individuals, a similar association of numbers and space appears in the form of an implicit mental number line as signified by the distance effect-reaction time decreases as the numerical distance between compared numbers increases. In the current experiment, three number-form synesthetes and two different non-synesthete control groups (Hebrew speaking and English speaking) performed a number comparison task. Synesthete participants exhibited a sizeable distance effect only when presented numbers were congruent with their number-form. In contrast, the controls exhibited a distance effect regardless of congruency or presentation type. The findings suggest that: (a) number-form synesthesia impairs the ability to represent numbers in a flexible manner according to task demands; (b) number-form synesthesia is a genuine tangible experience, triggered involuntarily; and (c) the classic mental number line can be more pliable than previously thought and appears to be independent of cultural-lingo direction.